Pengaruh Suplementasi Pakan Konsentrat Mengandung Tepung Ubi Kayu dan Tepung Bonggol Pisang dengan Level Berbeda terhadap Status Fisiologis Sapi Bali Penggemukkan Pola Peternak : The Effect of Suplementation of Concentrate Feed Containing Cassava Flour and Banana Hump Flour with Different Levels on Physiological Status of Fattening Bali Cattle Farming Pattern - Mana'o, Reinhart Jonathan; Rosnah, Upik Syamsiar; Sulistijo, Edi Djoko (Universitas Nusa Cendana, 2024)
The purpose of this study was to find out what the effects of supplementation of concentrate feed containing cassava flour and banana weevil flour had on the physiological status of Bali cattle fattening by breeders in Oeletsala Village. There were 4 cattle used in this study aged around 11.5 years with a body weight of around 133-155kg (x ̅ 144kg ± 10.2kg and KV 6%). The design used was the Latin Square Design (RBSL) consisting of 4 treatments and 4 periods as replications. The research treatment was P0: Farmer pattern ration + concentrate (40% banana hump and 60% cassava). P1: Farmer + concentrate ration (50% banana hump and 50% cassava). P2: Farmer's pattern ration + concentrate (60% banana hump and 40% cassava). P3: Farmer + concentrate ration (70% banana hump and 30% cassava). The results showed that the average rectal temperature (0C) P0 = 37.80 ± 0.198, P1 = 37.97 ± 0.125, P2 = 37.96 ± 0.177, and P3 = 37.97 ± 0.414; heart rate (beats/minute) P0= 79.56 ± 0.227, P1 = 78.13 ± 0.135, P2 = 77.69 ± 0.304, P3 = 78.94 ± 0.169 ; respiratory rate (times/minute) P0= 30.60 ± 0.196, P1 = 29.69 ± 0.232 P2 = 27.75 ± 0.137 P3 = 29.06 ± 1.434. The results of statistical analysis showed that physiological status did not differ between treatments (P>0.05). It was concluded that statistically the supplementation of concentrate feed containing cassava flour and banana weevil flour at different levels gave the same response and the physiological status of Bali cattle was fattening by breeders in normal circumstances. Tujuan dilakukannya penelitian ini untuk mengetahui apa saja yang ditimbulkan dari suplementasi pakan konsentrat mengandung tepung ubi kayu dan tepung bonggol pisang terhadap status fisiologis sapi Bali penggemukan pola peternak di Desa Oeletsala. Ternak sapi yang digunakan dalam penelitian 144kg ± 10,2kg dan KV 6%). Rancangan yang digunakan Rancangan Bujur Sangkar Latin (RBSL ) terdiri 4 perlakuan dan 4 periode sebagai ulangan. Perlakuan penelitian yaitu P0: Ransum pola peternak + konsentrat (bonggol pisang 40% dan ubi kayu 60%). P1: Ransum pola peternak + konsentrat (bonggol pisang 50% dan ubi kayu 50%). P2: Ransum pola peternak + konsentrat (bonggol pisang 60% dan ubi kayu 40%). P3: Ransum pola peternak + konsentrat (bonggol pisang 70% dan ubi kayu 30%). Hasil penelitian menunjukkan bawah rataan suhu rektal (0C) P0= 37,80±0,198, P1= 37,97±0,125, P2= 37,96±0,177, dan P3=37,97±0,414 ; denyut jantung (kali/menit) P0= 79,56±0,227, P1=78,13±0,135, P2= 77,69 ±0,304, P3= 78,94±0,169 ; frekuensi pernapasan (kali/menit) P0= 30,60±0,196, P1=29,69±0,232 P2= 27,75±0,137 P3= 29,06 ±1,434. Hasil analisis statistik memperlihatkan status fisiologis tidak berbeda diantara perlakuan (P>0,05). Disimpulkan bahwa secara statistik suplementasi pakan konsentrat mengandung tepung ubi kayu dan tepung bonggol pisang dengan level berbeda memberikan respon yang sama dan status fisiologis ternak sapi Bali penggemukan pola peternak dalam keadaan normal.